Multi-Attribute Task Battery configuration to effectively assess pilot performance deterioration during prolonged wakefulness. (2022) - Kong, Youngsun; Posada-Quintero, Hugo F.; Gever, David; Bonacci, Lia; Chon, Ki H.; Bolkhovsky, Jeffrey
Abstract: Multi-Attribute Task Battery (MATB) simulates realistic and complex aviation-related tasks a pilot routinely performs during flight. However, past studies using MATB have been unable to consistently elicit the effects of performance degradation during prolonged wakefulness. We surmise that this is because the task difficulty level of the MATB software was set too low. The MATB test that was designed for this protocol includes four tasks: system monitoring (SYSMON), communication (COMM), resource management (RESMAN), and all three tasks performed simultaneously. Twenty subjects performed a "session" consisting of both the psychomotor vigilance task (PVT) and the MATB test every 2 h over 25 h of prolonged wakefulness (i.e., for thirteen sessions). The difficulty levels were set to low for both SYSMON and COMM tasks, medium for RESMAN, and high for completion of the three tasks simultaneously, based on NASA task load index. We then calculated the correlation between PVT and MATB indices. As in previous studies, all PVT performance measures were significantly degraded in the last 2–4 sessions of the task, relative to sessions earlier in the 25-hr period. MATB indices were highly correlated with PVT indices. Moreover, all MATB tasks showed significant performance degradation during prolonged wakefulness unlike previous studies. Finally, the considerably more difficult multitasking required by the three simultaneous tasks led to a more consistent and higher degree of performance degradation with prolonged wakefulness than did most of the single tasks, which were set to either low or medium difficulty level. Thus, our results support the hypothesis that previous work failed to show significant performance degradation with prolonged wakefulness during the MATB due to inadequate levels of task difficulty. Our results provide evidence that the MATB, if set to an appropriate level of difficulty, can be used as an alternative to the PVT to more accurately study the effects of prolonged wakefulness on performance of realistic aviation tasks.